(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To know about the role of dynamization in fracture healing of femoral shaft fracture fixed with interlocking intramedullary nail. Methods: This prospective comparative study was conducted between January 2015 to July 2016 orthopedics department of PIMS hospital. Inclusion and exclusion criterion were determined. Patients were stratified randomly into non dynamized (Group A) and dynamized (Group B) groups. At six weeks dynamization was performed. Results: 60 patients (30 in each group) were included in the study. The mean age was 34.16±10.03 years. In group A, 21(70%) patients were male and 9(30%) were female. In group B, 23 (76.7%) patients were male and 7 (23.3%) were female. Fracture union rate was compared between the two groups. Conclusion: Although Dynamization reduces the time of union of fracture, it has no effect on rate of fracture healing,